An Investigation of Reliability and Life Time Prediction for Power MOSFET Using Electronically and Statistical Technique - Abdul-hasan Abdallah Kadhim; Munaf Fathi Badr; Abdulkhaliq A.AL-Naqeeb (Engineering and Technology Journal, 2013)
This work is aimed to estimate the life time of the MOSFET power transistor through an empirical implementation work merged with statistical applications. In the empirical part the MOSFET power transistors are subjected to high frequency(50kHz) via an electronically controlled model using advanced driving circuit (IR2113) that reduce the Miller effect of load side reflected to the transistor gate, so minimum voltage noise , to obtain accurate results. The statistical approach is based on developing simulation technique using Weibull distribution to estimate the life time of MOSFET power transistor. Two methods (maximum likelihood and order regression) were applied for simulated data of the actual performance to provide an accurately prediction of the failure time. The transistor was tested by supply variable voltages from zero to break down voltage and different results are observed. The results show that the first of the suggested method gives a best performance for simulation results compared with the two of the conventional methods.